Upaya Pengendalian Penyakit Hipertensi dan Diabetes Mellitus melalui Peningkatan Peran Kader Kesehatan - Aid Fitriyana Hidayat; Angga Musyaffa; Ai Reny Rahmawati; Dita Nurlela; Johan Budhiana; Nur Hidayat; Mamlukah Mamlukah (Kolaborasi: Jurnal Pengabdian Masyarakat, 2023)
Introduction: Non-communicable diseases (NCDs), especially hypertension and diabetes mellitus, are among the leading causes of death in Indonesia. Increasing cases of these two cases are expected to add to the burden on society and government. The role of cadres is very important in efforts to control these two diseases. Objective: The purpose of community service is to improve the knowledge, motivation and attitude of health cadres through education. Method: Education was conducted on participants. Evaluation was conducted using pretest and posttest methods to measure knowledge, attitude, and motivation. The subjects used were health cadres in the working area of Tinewati Health Centre as many as 40 people. Result: The results showed that education did not improve hypertension knowledge (p=0.083) and diabetes mellitus knowledge (p=0.323) in health cadres. Education increased hypertension motivation, diabetes mellitus motivation, and attitude in health cadres (p=0.000). Conclusion: The conclusion shows that education increases the motivation and attitude of cadres. It is expected that the Tinewati Health Centre to carry out education to health cadres on an ongoing basis in an effort to help control NCDs of hypertension and diabetes mellitus.